Membuat Video Animasi Penjualan dengan Canva Pada Karang Taruna Rw.06 Jalan Mampang Prapatan - Muhammad; Yamin Nuryamin; Muhammad Fahmi; Siti Nurdiani (Indonesian Community Service Journal of Computer Science, 2024)
This community service aims to provide training to Karang Taruna members in the skills of making animated sales videos using the Canva platform. Karang Taruna is a youth organization that plays an active role in community development at the local level. Participants will be introduced to using Canva, including how to create an account and choose a suitable template for sales promotion purposes. They will learn the basic steps in arranging design elements such as text, images, and icons to create engaging videos. Next, the training will focus on techniques for using animation elements to add dynamic elements to videos. Participants will practice how to incorporate animation into text, images, and other design elements to increase the appeal of videos. During the training, there will be a discussion regarding marketing and visual communication strategies that can help Karang Taruna members maximize the effectiveness of animated videos in their sales campaigns. At the end of the program, Karang Taruna members will have the skills to create high-quality animated videos with Canva. They will be able to use these skills to promote Karang Taruna's activities and initiatives, as well as support product or service sales efforts within their communities. It is hoped that this training can increase the competitiveness and positive impact of Karang Taruna in the local community.